Leveraging innovative technology to generate drug response phenotypes for the advancement of biomarker‐driven precision dosing - Akinyemi Oni‐Orisan; Nithya Srinivas; Krina Mehta; Jesmin Lohy Das; Thu T. Nguyen; Geoffrey H. Tison; Scott R. Bauer; Maria Burian; Ryan S. Funk; Richard A. Graham; Biomarkers and Translational Tools Community Working Group of the American Society for Clinical Pharmacology and Therapeutics (Wiley, 2021)
Abstract Although traditional approaches to biomarker discovery have elucidated key molecular markers that have improved drug selection (precision medicine), the discovery of biomarkers that inform optimal dose selection (precision dosing) continues to be a challenge in many therapeutic areas. Larger and more diverse study populations are necessary to discover additional biomarkers that provide the resolution needed for a more tailored dose. To generate and accommodate large datasets of drug response phenotypes, time‐ and cost‐efficient strategies are necessary. In particular, a multitude of technological advances that originated for purposes outside of biomedical research (electronic health records, direct‐to‐consumer genetic testing, social media, mobile devices, and machine learning) have made it easier to communicate, connect, and gather information from consumers. Although these technologies have been used with success in the health sciences for an array of purposes, these resources have not been fully capitalized on for precision dosing. This perspective will touch on how these innovations can be used as data sources, data collection tools, and data processing tools for drug‐response phenotypes with a unique focus on advancing biomarker‐driven precision dosing.